De novo transcriptome assembly reveals three alternative oxidase encoding genes in Nymphaea alba L. - Ercan Selçuk Ünlü; Gülgez Gökçe Yıldız (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2022)
Water lilies are aquatic, ornamental and economically valuable plants classified under Nymphaea genus. Nymphaea alba L., white water lily, has a special focus since it is a member of basal angiosperms. Alternative oxidase (AOX) proteins are the terminal oxidases in the electron transport chain of plants. Identification of alternative oxidase encoding genes for basal angiosperms is important to increase the quality of phylogenetic studies. However, AOX encoding genes were yet to be discovered for N. alba. In this study, we aimed to identify alternative oxidase encoding genes in N. alba by performing transcriptome analysis. Annotation of 272,934 unigenes with Trinotate tool revealed 77 transcripts with AOX domains characterized in known alternative oxidases. Blast analysis of these 77 sequences with known AOX proteins revealed three distinct AOX genes (AOX1, AOX2 and AOX4) in N. alba. After in silico subcellular localization analysis of three identified AOX proteins, AOX1, AOX2 are predicted as mitochondrial while AOX4 is a plastidic alternative oxidase protein. Template-based structural modeling results showed that all identified proteins are statistically similar to known structure models of corresponding AOXs.